Efektivitas Aplikasi Mobile Learning Role Play Games (RPG) Maker MV untuk Meningkatkan Kemampuan Berpikir Kritis - Abdur Rasyid; Aden Arif Gaffar; Widi Utari (Universitas Wiralodra, 2020)
Student learning activities that are less conducive, passive in asking questions and answering questions from problems raised by teachers, difficult to express ideas or ideas of problem solving and the learning process provided, and have not been oriented to develop students' critical thinking skills.The purpose of this study is to determine the feasibility, find out the increase in students' critical thinking skills, and to find out students' responses to the application of RPG maker MV based mobile learning applications in the learning ecosystem. The research method used is Quasi-Experimental, the design used in this study is Quasi-Experimental Design with Randomized Control-Group Pretest-Postest. The data obtained in this study consisted of qualitative data, namely the results of observations of student activities during learning and student questionnaire responses to the application of mobile learning applications based on RPG maker MV, and quantitative data namely the results of students' critical thinking abilities. The results showed (1) the implementation of the RPG maker MV based mobile learning application has moderate criteria, (2) the application of the RPG maker MV based mobile learning application can improve students 'critical thinking skills, (3) students' responses to the use of RPG maker based learning mobile applications MV in ecosystem learning has very good criteria.